Optimization of power optical transmission network based on photo-electronic hybrid cross-connection technology - Yang ZHAO; Wei SONG; Chengyu DUAN; Fang SHEN; Xiaohong ZHANG; Jihua ZHAO (Dianxin kexue)
A preliminary analysis to the current situation of the power grid optical transmission network was made.The power grid optical transmission network is facing huge challenges such as the increasing transmission capacity, the increasingly complex topology, the flexible scheduling of services and the evolution of network intelligence.By adopting photoelectric layered cross processing, electric layer cross focus on small particles business convergence and long distance electric regeneration, optical layer routing provides the flexible wavelength routing, based on colorless, directionless, and contention less flexible grid configurable add/drop architecture CDC-F ROADM technology to optimize network structure, improve the network transmission efficiency, reducing energy consumption and space, which also benefits the evolution of network intelligence, and greatly save the construction and operational costs.